Temporal and Spatial Variation of Soil Salinity Variations in a 24-year Period in Abadan District Using Satellite Images - Mehdi Mumipour (جغرافیا و پایداری محیط)
Soil Salinity caused by poor water and soil resources management and non- sustainable agriculture, lead to the decrease of soil productivity. In traditional soil salinity measurements, soil samples are collected from field and analyzed for electrical conductivity. Remote Sensing data and techniques are more effective and frugal for soil salinity monitoring. Surface salts spectral reflectance are studied widely as a direct evidence of saline soils. This study aims to distinguish spatial and temporal variation of saline soils in Abadan district. For this purpose, Landsat images with a 24 –year interval were used in conjunction with field data. Three indices including B/G, NDSI and SI extracted from images. Linear regression used for assessment of indices and results shows that SI index is more compatible with field data (R2=0.573). In the period of this study, soil salinity in some parts of the district has been decreased and in some other parts has been increased. The indices are not acceptable in the absence of field data. This study shows that soil salinity in Abadan district has decreased in the period of the study. However, the soil salinity is above the standard levels, except in few parts that soil salinity has been increased. Satellite images and salinity indices are useful to make an overview of soil salinity, but data uncertainty should be indicated. Extended Abstract 1-Introduction In the traditional soil salinity measurement methods, samples are collected from field and analyzed in the laboratory to determine the concentration of soluble substances or electrical conductivity (EC). However, these methods are time consuming and costly, because they need large amount of sampling to determine the spatial variation of soil salinity in an area. Unlike traditional methods, remote sensing techniques are more effective and frugal method to monitor the soil salinity and salinity map preparation. Halophyte plants on the soil surface can be a sign of soil salinity, which enables indirect detection of saline soils based on the spectral signature of the vegetation. Normally, unhealthy or salt-affected plants have less photosynthesis activity, which lead to more reflection in the visible and less reflection in near-infrared (NIR) spectrum which is referred as salt stress in plants. Several vegetation indices such as NDVI, SAVI are used as indirect indices of soil salinity. Besides, some researchers have introduced salinity indices that are directly applicable to salinity detection, such as NDSI and SI. The purpose of this study was to investigate the spatial and temporal changes in salinity of surface soils in Abadan district. For this purpose, Landsat satellite imagery has been used for a 24-year period from 1990 to 2014. Three soil salinity indices have been applied on satellite images and compared to illustrate changes in soil salinity and shows which indices are more suitable for the study area? 2-Materials and Methods The study area is Abadan district, located at Iran-Iraq political border in the southwest of Iran. The annual precipitation of the study area is less than 250 mm per year. This area has been affected by saline water in recent years and soil productivity had been decreased. The satellite image of TM Landsat 5 (1990) and OLI Landsat 8 (2014) were used. The usual radiometric and atmospheric corrections were done for these images. The regression was done based on the Landsat 8 data that was simultaneous with soil sampling. The salinity indices used in this study includes the Normalized Differential Salinity Index (NDSI), the ratio of blue to green bands and Salinity Index (SI):